9(12s-7)+20=7(15s+2)

Simple and best practice solution for 9(12s-7)+20=7(15s+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(12s-7)+20=7(15s+2) equation:


Simplifying
9(12s + -7) + 20 = 7(15s + 2)

Reorder the terms:
9(-7 + 12s) + 20 = 7(15s + 2)
(-7 * 9 + 12s * 9) + 20 = 7(15s + 2)
(-63 + 108s) + 20 = 7(15s + 2)

Reorder the terms:
-63 + 20 + 108s = 7(15s + 2)

Combine like terms: -63 + 20 = -43
-43 + 108s = 7(15s + 2)

Reorder the terms:
-43 + 108s = 7(2 + 15s)
-43 + 108s = (2 * 7 + 15s * 7)
-43 + 108s = (14 + 105s)

Solving
-43 + 108s = 14 + 105s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-105s' to each side of the equation.
-43 + 108s + -105s = 14 + 105s + -105s

Combine like terms: 108s + -105s = 3s
-43 + 3s = 14 + 105s + -105s

Combine like terms: 105s + -105s = 0
-43 + 3s = 14 + 0
-43 + 3s = 14

Add '43' to each side of the equation.
-43 + 43 + 3s = 14 + 43

Combine like terms: -43 + 43 = 0
0 + 3s = 14 + 43
3s = 14 + 43

Combine like terms: 14 + 43 = 57
3s = 57

Divide each side by '3'.
s = 19

Simplifying
s = 19

See similar equations:

| -3x-9x=72 | | 9(t-2)+3t=4(3t+3)-9 | | -6(-3r-11)=13r-10+9r | | 10+13=12n-3 | | 22x-6-12x+2=25x-5-15x+14 | | -2x-3=-2x+6 | | -6=n/2-1 | | 0=16t^2+48t-36 | | -7x-11=8x+11 | | -x/5=-2/5 | | 5/3s=15/3+3/25-1/4 | | 4(x-3)=3(x-8) | | 3(11b+11)=-4(-9b-9) | | 3p/2=-3 | | 16p-.6=7p+4 | | s+8.8=6.2 | | 2(3x-2)+7=133 | | 10c+2+13c=-8c+9(4c-7) | | 8+8k+10=k | | v/3+9=8 | | -195=-5x+5(-2x+-9) | | 3x+30/6+x+24/5=14 | | 2(11)-7(3)=1 | | X-18.7=-12 | | 2a+3b=-4 | | -7+g=-27 | | .25x+6=.667x+28 | | 3/4(x+3)+15 | | 7(-m-16)=-3m+17m+14 | | 0=16t^2+48-36 | | 12x^2/15x^2 | | (1/8)X+(1/4)=(1/6)X+(2/15) |

Equations solver categories